Analisis Strategi Cina Melakukan Foreign Direct Investment (FDI) berbasis Minyak dengan Sudan Tahun 2009 - Putri, Syelda Titania Sukarno; Gamaly, Gamaly; Dwi, Yolanda (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
The rapid economic growth of China during the last two decades, has prompted its dependence on oil imports exceeding its domestic production. China for the first time exceeded the US position as the biggest oil importer in 2015 in Africa region particularly Sudan. Chinese oil investment in Sudan then become an international concern because China's non-intervention policies are considered irresponsible of domestic problems in Sudan. This research attempts to explain Cina’s strategic interaction with conflict-troubled Sudan using three analytical variables, (i) the identification of state interest; (ii) the specification of strategic setting with Cina First; and (3) the impact of the Cina investment to Sudan. The analysis result shows that Cina’s need for oil to secure its economic growth is Cina’s vital interest as being prioritized by they strategic based on Cina’s First policy that is permissive towards Sudan’s domestic issue.